Tobacco-Free Areas Implementation at University X - Fitri, Tari Adelia; Suryoputro, Antono; Nandini, Nurhasmadiar (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2023)
Introduction: University X is one of the institutions where tobacco-free areas are required in a university setting where teaching and learning activities are highly regulated. However, the implementation of tobacco-free was only implemented in a few faculties, and, the whole academic community of University X has not entirely complied with the regulation. This study aimed to analyze the implementation of Tobacco-Free Areas at University X.Methods: This study used a qualitative research method to examine the implementation of smoke-free areas at University X. Data were gathered through in-depth interviews, observations, and other supporting documentation. There were 13 research informants, including Deans/Vice Deans from four faculties, the Academic Director of Student Affairs, alumni, lecturers, and students of University X. This study examined communication, resources, disposition, and bureaucratic organization policies.Results: This study found that university administrators never communicated directly or indirectly regarding Tobacco-Free Areas regulation. It is still neither excellent nor adequate, based on the resources available for human resource compliance and infrastructure availability. In terms of disposition, numerous parties fully support the execution of the smoke-free policy. However, the implementing officers/supervisors of the smoke-free areas at University X were less steadfast. This is demonstrated by the absence of a bureaucratic framework at University X in implementing and supervising Tobacco-Free compliances.Conclusion: Tobacco-free areas had been implemented at University X although they were not yet complete and optimal. It is possible to infer that this was not a priority at University X because conflicts of interest might hamper this regulation, resulting in lacking clarity, and sustainability.